Do Fewer People Mean Fewer Cars? – Population Decline and Car Ownership in Germany - Nolan Ritter; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Drawing on household data from Germany, this study econometrically analyzes the determinants of automobile ownership, focusing specifically on the extent to which decreases in family size translate into fewer cars at the national level. Beyond identifying several variables over which policy makers have direct leverage, including the price for fuel, the supply of public transit, and land use features, the analysis uses the estimated coefficients from a multinomial logit model to simulate car ownership rates under alternative scenarios pertaining to demographic change and other socioeconomic variables. Our baseline scenario predicts continued increases in the number of cars despite decreases in population, a trend that could be partially offset by substantial increases in fuel prices. – – Diese Studie untersucht die Determinanten des privaten Fahrzeugbesitzes anhand eines multinomialen Logit-Modells und Haushaltsdaten aus Deutschland. Dabei wird insbesondere der Einfluss der Haushaltsgröße betrachtet. Die Studie kontrolliert für eine Vielzahl von Variablen, auf die die Politik einen erheblichen Einfluss ausübt. Dazu zählen etwa der Kraftstoffpreis, das Angebot des öffentlichen Verkehrs oder die Bebauungsplanung. Die Ergebnisse der multinomialen Logit-Schätzung werden verwendet, um die Gesamtanzahl von Fahrzeugen im Privatbesitz unter alternativen Szenarien zur demographischen und sozio-ökonomischen Entwicklung bis zum Jahr 2030 zu prognostizieren.
Keywords: C25; D10; R41; 330; car ownership; demographic change; Germany; multinomial logit; simulation